Representasi Perempuan Berhijab Dalam Iklan Televisi (Analisis Semiotika pada Iklan Rejoice 3 In 1 Versi Hijabisa dan Sariayu Hijab Care Series Versi Bebas Berhijab) - Sri Rahayu; Ida Ri'aeni; Rizki Budhi Suhara (Universitas Majalengka, 2021)
Every advertisement have a message, including advertisement for Rejoice 3 In 1 Hijabisa version and Sariayu Hijab Care Series Hijab Free version. Two messages that are interconnected and interpreted as a sign who interpret and present concepts and ideas or feelings in such a way which allows one to read and interpret the meaning. Advertisements that both promote a product for women, especially muslimah with hijab, not only to strengthen the product but there is an interesting message especially about hijab women (muslimah). The purpose of the study was to find out the representation of hijab women in the denotation, connotation and. This study uses qualitative method with Roland Barthes's semiotic analysis. Barthes divides the process of tagging order, namely denotation, connotation and myth. This research resulted in research findings on the two advertisements which model activities, settings, interesting ways, jingles and narratives and other properties presented in both advertisements.